Trophic guilds of EPT (Ephemeroptera, Plecoptera, and Trichoptera) in three basins of the Brazilian Savanna - Ceneviva-Bastos, Mônica [UNESP]; Prates, Dayane Boracini [UNESP]; de Mei Romero, Renato; Bispo, Pitágoras Conceição [UNESP]; Casatti, Lilian [UNESP] (Elsevier, 2017)
Insects of the orders Ephemeroptera, Plecoptera, and Trichoptera (EPT) are prominent among stream biota and are associated with many ecological processes in these environments, meaning that a proper definition of their habits is essential. We studied EPT from three watersheds in Brazil (Paraguai, Paraná, and São Francisco) in order to (i) determine the trophic guilds of EPT genera sampled; (ii) determine whether trophic guilds reflect EPT phylogenetic component (taxonomic distance); (iii) compare trophic guild composition among watersheds; and (iv) verify the effect of environmental components in trophic guild composition. Eight trophic guilds were determined based on gut content analysis: detritivores, fine-detritivores, fine-detritivores/algivores, coarse-detritivores, coarse-detritivore/algivores, periphytivores, carnivores, and omnivores. Caddisflies presented the most variable diet and many genera belonged to different trophic guilds in different basins. Overall trophic guild composition did not reflect the taxonomic distance among taxa and it did not differ among the three basins. Instead, EPT guilds were related to local environmental variables, evidencing that their diet probably varies according to local resource availability, highlighting the importance of empirical assessments of diet for ecological studies.
Keywords: Aquatic insects; Diet analysis; Functional feeding groups; Macroinvertebrates; Streams